Review: Research progress of adipose-derived stem cells in the treatment of chronic wounds - Hao, Zhuolun; Qi, Wenli; Sun, Jiaming; Zhou, Muran; Guo, Nengqiang (Frontiers in Chemistry, 2023)
Various methods are used to treat wounds clinically, but there are still many difficulties in the treatment of chronic wounds due to an excessive inflammatory response, difficulties in epithelialization, vascularization, and other factors. With the increasing research on adipose-derived stem cells (ADSCs) in recent years, many evidences show that ADSCs scan promotes the healing of chronic wounds by regulating macrophage function and cellular immunity, promoting angiogenesis and epithelialization. In order to provide reference for the stem cell therapy of chronic wounds, this paper reviewed the difficulties in the treatment of chronic wounds, the advantages and the mechanism of ADSCs in promoting the healing of chronic wounds.